Impact of COVID-19 on mortality in the elderly population of Cordoba, Argentina. Preliminary analysis of the first two years of the pandemic - Pelaez, Enrique (2024)
Introduction: This paper aims to analyse the impact of the COVID-19 pandemic during 2020-2021 in Córdoba (Argentina) on older people, measured by excess deaths (ED) and change in life expectancy (LE). Methodology: Data sources used were deaths for the period 2017-2020, from the national Ministry of Health. Life tables were calculated for the three-year periods 2017-2019, 2020 and 2021. Finally, the decomposition of EV differences in 2020 and 2021 was calculated. Results: There were 10.3% excess deaths in 2020 and 25.5% in 2021, higher in males. ED was concentrated in the over-60s, although in 2021 mortality in young adults was significant. In 2020 the ED rate in males over 80 is three times higher than in the 60-79 years group. There is a marked bias between males and females. In 2021 there are fewer differences between ages and sexes, although the higher rate for males over 80 remains. In 2020 COVID deaths accounted for 74.2 per cent of ED for males and 102.4 per cent for females; in 2021 they accounted for 60.2 per cent and 57.7 per cent respectively. The EV loss in 2020 was 0.83 years in males and 0.26 in females; in 2021, 2.73 and 2.25 years respectively. Older males concentrate the decline in EV in infectious diseases and COVID-19. Conclusions: Knowledge of the impact of the pandemic on older people provides valuable evidence for health policy planning.